대체 보조전극을 이용한 접지저항 측정 신뢰성 분석 - 李尙益(Sang-Ick Lee); 兪在根(Jae-Geun Yoo); 全正采(Jeong-Chay Jeon); 全炫栽(Hyun-Jae Jeon) (전기학회 논문지 P권, 56(2), 2007)
This paper summarize about the auxiliary electrode measured a ground resistance. The method to measure a ground resistance is the fall-of-potential method to using an auxiliary electrode. And an auxiliary electrode must be set up on the ground. Today it is so difficult to set up the auxiliary electrode on the ground because of many concrete building and many paved roads. So this paper is regarding a trust analysis of the ground resistance measurement by the substitute auxiliary electrode. It substituted a iron structure around the building, a neutral line multiplex ground to earth, a wire net for auxiliary electrode. This information is confirmed bv compared with the measurement value.